2006
DOI: 10.2320/matertrans.47.283
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Mechanical Properties of Porous Co–Cr–Mo Alloy Compacts without Ni Addition

Abstract: Porous Co-29Cr-6Mo (mass%) compacts without Ni were fabricated by hot pressing and their microstructure and mechanical properties were investigated. PREPed Co-29Mo-6Mo powder with a diameter range (300-500 mm) was hot-pressed under the uniaxial pressure of 40 MPa at 1223 K for 7.2 ks. Hot-pressed compacts were annealed at 1473 K for 7.2 ks for further sintering. X-ray diffraction analysis revealed that and " phases appeared dominantly in the PREPed powder, while " and phases coexisted in the compact which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…2 shows X-ray profiles of Co-29Cr-6Mo compacts hot-pressed at 1223 K and 40 MPa for 7.2 ks in vacuum or nitrogen atmosphere. In the V compact, the ε phase exists dominantly and the phase is weakly confirmed, which agree with the previous study [4]. In the N compacts, the γ phase is observed.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2 shows X-ray profiles of Co-29Cr-6Mo compacts hot-pressed at 1223 K and 40 MPa for 7.2 ks in vacuum or nitrogen atmosphere. In the V compact, the ε phase exists dominantly and the phase is weakly confirmed, which agree with the previous study [4]. In the N compacts, the γ phase is observed.…”
Section: Resultssupporting
confidence: 92%
“…The porous Co-Cr-Mo coating on the implants as well as the substrate Co-Cr-Mo alloy, should not contain Ni since the release of metal ions at the large interface between body fluid and metal [3] presents great concern. In the previous paper, the mechanical properties of the porous Co-Cr-Mo alloy compacts without adding Ni were evaluated [4]. The as-hot-pressed compact shows the limited elongation because the σ phase precipitates during sintering.…”
Section: Introductionmentioning
confidence: 99%
“…The lamellar function gives the information about the distance between the layers. Nomura et al 37 and Telu et al 38 also examined the lamellar formation of Co-Cr alloys by using XRD analysis. Telu et al 38 showed that decreasing the bilayer thickness increased the homogeneity of the alloy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the compressive strength of the compacts with porosity of that range is slightly lower than that of the human bone. In order to improve the strength, Nomura et al (6), (7) prepared nitrogen added porous Ti compacts and porous Ti-15Mo-5Zr-3Al compacts.…”
Section: Introductionmentioning
confidence: 99%